Analisis Kompetensi Karyawan Departemen PPIC pada Salah Satu Perusahaan Pupuk Swasta di Kabupaten Gresik - Putri Andini Sekar Sari; Maulidyah Amalina Rizqi (Universitas Nusantara PGRI Kediri, 2025)
This research aims to measure the competencies of employees in the PPIC department at a private fertilizer company in Gresik Regency and evaluate the existing recruitment and selection processes. Using a qualitative descriptive approach, the research collected primary data through in-depth interviews with HRD, PPIC Leaders, and employees with and without relevant experience. Data were analyzed using the Miles and Hubman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results reveal a competency gap among PPIC employees, primarily caused by suboptimal recruitment and selection processes, leading to mismatches between candidates' qualifications and job requirements. Employees without relevant experience face difficulties in performing technical tasks, affecting the department's productivity and efficiency. This study emphasizes the need for a more structured recruitment and selection process and targeted formal training to enhance employee competencies.